Fostering Creativity through Technology-Enhanced Learning Environments - Dzikri , Ahmad Sidiq; Afriani, Gusma; Krisnawati , Nova (Civiliza Publishing, Indonesia., 2025)
This study explores the role of technology-enhanced learning environments (TELEs) in fostering creativity among students, addressing concerns that traditional education often stifles creative potential. The research aims to examine how digital tools and pedagogical strategies can be designed to support creative thinking in diverse educational contexts. Using a qualitative approach, the study involved observations, interviews, and analysis of digital learning artifacts across multiple secondary schools and a university in Yogyakarta, Indonesia. Findings reveal that TELEs, when combined with learner autonomy, collaborative platforms, and multimodal expressions, significantly enhance creativity. However, the successful integration of these environments depends on teachers' digital competence, institutional flexibility, and equitable access to technology. The study concludes that fostering creativity through technology requires intentional pedagogical design and systemic support.